KOMPARASI HASIL BELAJAR MATEMATIKA MENGGUNAKAN PEMBELAJARAN AKTIF PEER LESSONS DENGAN TEAM QUIZ SISWA KELAS VIII SMP NEGERI 51 MERANGIN - M. Jainuri (Pendidikan Matematika | STKIP YM Bangko, 2022)
The purpose of this study is to describe the learning outcomes of mathematics using the active peer lessons learning model, which is better than the team quiz learning model. This study uses a quantitative approach with experimental research methods. The population of all students of class VIII SMP Negeri 51 Merangin, totaling 2 classes. Sampling using probability sampling type simple random sampling, selected class VIIIA as experimentalclass 1, and class VIIIB as experimental class 2. The technique of collecting data on mathematics learning outcomes used was a test. The instrument is in the form of essay questions, totaling 10 questions. The data analysis technique used the t-test formula, because the data were normally distributed and the variance was homogeneous. From the analysis of the test results, it is known that the average value of the experimental class 1 is 66.47, and the average value of the experimental class 2 is 63. Hypothesis test analysis using the t-test shows that the p value is 0.096 > 0.05, so H0 rejected. Ha is accepted. It can be concluded that the results of learning mathematics using the peer lessons learning model are better than the team quiz model for class VIII students of SMP N 51 Merangin.